2021
DOI: 10.1021/acs.jpclett.1c03570
|View full text |Cite
|
Sign up to set email alerts
|

Twist-to-Untwist Evolution and Cation Polarization Behavior of Hybrid Halide Perovskite Nanoplatelets Revealed by Cryogenic Transmission Electron Microscopy

Abstract: Hybrid methylammonium lead iodide (MAPbI3) perovskite nanoplatelets (NPLs) have emerged as promising optoelectronic materials because of their remarkable properties in defect tolerance, band gap tunability, and light emission. However, the detailed formation mechanism, in particular the atomic structure information in the initial nucleation stage, stands as a mystery because of the intrinsic vulnerability toward moisture, electron beams, etc. By virtue of the imaging technique under the extremely low electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This technique even holds promise for quantifying the polarization offset of the methylammonium (MA) cations based on the ideal position of the tetrahedral center, akin to methods employed for inorganic ferroelectric perovskite materials. [79] Our collaborators, led by Loh, synthesized three Mn-based hybrid perovskite single crystals with varying dimensionality by modifying the organic component within the organic-inorganic hybrid perovskite structure. [80] These materials consisted of a 2D material, (4-fluorobenzylamine (FB)) 2 MnCl 4 , a one-dimensional (1D) ((R)-3-fluoropyrrolidinium (FP))MnCl 3 , and a zerodimensional (0D) (pyridine (PD)) 2 MnCl 4 .…”
Section: Organic-inorganic Hybrid and All Organic Perovskitementioning
confidence: 99%
See 1 more Smart Citation
“…This technique even holds promise for quantifying the polarization offset of the methylammonium (MA) cations based on the ideal position of the tetrahedral center, akin to methods employed for inorganic ferroelectric perovskite materials. [79] Our collaborators, led by Loh, synthesized three Mn-based hybrid perovskite single crystals with varying dimensionality by modifying the organic component within the organic-inorganic hybrid perovskite structure. [80] These materials consisted of a 2D material, (4-fluorobenzylamine (FB)) 2 MnCl 4 , a one-dimensional (1D) ((R)-3-fluoropyrrolidinium (FP))MnCl 3 , and a zerodimensional (0D) (pyridine (PD)) 2 MnCl 4 .…”
Section: Organic-inorganic Hybrid and All Organic Perovskitementioning
confidence: 99%
“…Electron diffraction and HRTEM have been instrumental in elucidating structural complexities within inorganic perovskites and organic-inorganic hybrid perovskites, including ion polarization, structural distortions, vacancies, and grain boundary defects. [47,76,79,81,82] However, research on the crystal structures of all-organic perovskites, which lack metal cations, remains comparatively limited due to the challenges associated with both synthesis and characterization. The primary challenge in synthesizing all-organic perovskites stems from the substantial size difference between organic molecules and inorganic ions within the traditional ABX 3 perovskite structure.…”
Section: Organic-inorganic Hybrid and All Organic Perovskitementioning
confidence: 99%
“…Alternatively, Zhang et al employed a direct-detection electron-counting camera to obtain the first atomic resolution image of MAPbBr 3 at a total dose of only 11 e/Å 2 , revealing nanodomain structure where the MA + cations were ordered locally in the single crystal, as shown in Fig. 4(b) [39,81] . Chen et al also used direct-detection electron-counting camera to investigate the decomposition pathway of MAPbI 3 at atomic scale, where the intermediate phase of MA 0.5 PbI 3 with locally ordered vacancies was successfully imaged [82] .…”
Section: Emerging Tem Approaches For Halide Perovskites At Atomic Res...mentioning
confidence: 99%
“…Rothmann et al were one of the first research groups to report twinning structure in the as-grown MAPbI 3 single crystal sample using electron diffraction [38] . The atomic-resolution structure of MAPbI 3 was further revealed using direct electron detector and cryo-TEM, respectively [39,40] . Yu et al reported a nanodomain structure in CsPbBr 3 2D nanocrystals where tetragonal and cubic phases coexist [41] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation